Bioequivalence Study of 2 Capsule Formulations of Fingolimod 0.5 mg Assessing Both Parent Drug and Active Metabolite in New Zealand Healthy Subjects (Truncated Design) - Hung, Noelyn Anne; Costa, Fernando Guillermo; Hung, Cheung‐Tak; Rosenberg, Mónica Esther (Clinical pharmacology in drug development, 2020)
Fingolimod is indicated for the treatment of patients with the relapsing‐remitting form of multiple sclerosis. The primary study objective was to evaluate the bioequivalence of a test formulation, 0.5 mg fingolimod HCl capsule (Lebrina, Asofarma Sociedad Anónima Industrial y Comercial, Argentina) relative to a reference formulation, 0.5 mg fingolimod capsule (Gilenya, Novartis Pharmaceutical, Australia). In a single‐center, randomized, single‐dose, single‐blinded, 2‐way crossover study, 33 New Zealand healthy subjects of both sexes were enrolled to receive a 0.5‐mg dose of 3 capsules of each fingolimod formulation under fasting conditions, with a 42‐day washout period between administrations. Additional pharmacokinetic information regarding its main active metabolite, fingolimod phosphate, was also provided. The point estimate and 90% confidence intervals of the ratios of maximum concentration and area under the plasma concentration–time curve from time 0 to 72 hours were 99.07 (95.83‐102.41) and 97.64 (95.33‐100.00) for fingolimod, and 95.60 (90.95‐100.49) and 98.54 (96.19‐100.96), for fingolimod phosphate. Primary parameters, maximum concentration and area under the plasma concentration–time curve from time 0 to 72 hours for fingolimod and fingolimod phosphate were found to have no significant difference when test and reference formulations were compared. Fingolimod and fingolimod phosphate of both formulations were within the accepted 90% confidence interval limits of 80.00% and 125.00%. No significant differences between the test and reference drug products were detected in any of the pharmacokinetic parameters estimated. Notwithstanding the primary conclusion of bioequivalence is focused on the measurement of the parent compound, compliance with the same criteria by the active metabolite reinforces the comparability between the pharmacokinetic profiles of both formulations (ClinicalTrials.gov Identifier: NCT03757338).